Vision and Innovation in Biology Education (VIBEnet) : Final Report. - Ross, Pauline; Taylor, Charlotte; Jones, Susan; Johnson, Elizabeth; Tzioumis, Vicky (Office for Learning and Teaching, 2014)
Final report from a project that established a network in university biology education. The network aims to: develop a national identity and network (VIBE.net) for university biology teachers, to build on the ALTC LTAS Science threshold learning outcomes and develop biology threshold learning outcomes; mentor the next generation of biology teachers (ie current sessional staff) to enhance active/inquiry learning in biology, particularly at the first year level, and to build teams of academics, sessional staff and students at the institutional level, in each state/region; and create a vision and innovation statement which reflects the collective understandings about the direction of the future biological curriculum, especially at first year level.